E-Customer Review, E-Customer Rating, E-Payment: Perbedaan Perspektif Konsumen Berdasarkan Gender - Paras Islami; Virgo Simamora (Cakrawala Repositori IMWI, 2023)
Because of its large population and high rate of internet penetration, Indonesia is a country that offers a tremendous opportunity for the digital market. This research is a descriptive and comparative study that seeks to explain differences in customer perspectives on e-customer reviews, e-customer ratings, electronic payments based on gender. This study's sample consists of men and women who have made purchases in Indonesian markets; the actual number is unknown. This survey includes 340 customers, with an equal number of female and male participants. The sampling technique used in this research is purposive sampling, in which all of the samples fulfilled the criteria of this research. The results of the study show that there are differences between men and women in online transactions. In the same way, men and women have different perspectives about e-customer reviews, e-customer ratings, and e-payments.